How multidimensional perceived value shapes online insurance purchase intention in China: The mediating role of attitude and the moderating role of eWOM - Cao, Sen; Mohammad, Jihad; Lee, Eva Lim Wei (Edelweiss Applied Science and Technology, 2026)
As digital transformation reshapes financial services worldwide, online insurance has become an increasingly important channel for insurers to reach consumers. In China, however, consumers’ intention to purchase insurance online remains uneven due to product complexity, information asymmetry, and perceived risk. This study examines how multidimensional perceived value shapes online insurance purchase intention in China, with attitude as a mediator and electronic word-of-mouth (eWOM) as a moderator. Grounded in perceived value theory and the value-attitude-behavior hierarchy, the study conceptualizes perceived value as emotional value, social value, functional value-price, and functional value-quality. Data were collected through an online questionnaire, yielding 663 valid responses. Partial least squares structural equation modeling (PLS-SEM) was used to assess the measurement model, structural model, mediation, moderation, and predictive relevance. The results show that all four perceived value dimensions positively and significantly affect attitude toward online insurance, while attitude significantly enhances purchase intention. Attitude also mediates these relationships, and eWOM positively moderates the attitude-purchase intention link. Overall, the findings show that online insurance adoption depends on value perceptions, favorable attitudes, and credible online communication, extending perceived value research in the digital insurance context and offering practical guidance for insurers.